Dimensions of trade policy - Richardson, Martin 1960- (World Scientific Publishing Co. Pte Ltd., 2018)
"Dimensions of Trade Policy collects the author's significant works on international trade policy over almost 30 years of publishing. The articles cover an eclectic range of topics but are grouped into three main areas of concentration — local content protection, the economics of preferential trading areas and the relationship between trade and competition policies — and the book also includes some sui generis topics, such as "fair trade" and "buy local" schemes. An introduction ties the chapters together and indicates their relevance to contemporary matters in trade policy."--Publisher's website
Description based on online resource; title from PDF title page (viewed November 17, 2017)
Keywords: Commercial policy; International trade; Electronic books